Advancing mRNA technologies for therapies and vaccines: An African context - Kairuz, Dylan; Samudh, Nazia; Ely, Abdullah; Arbuthnot, Patrick; Bloom, Kristie (Frontiers in Immunology, 2022)
Synthetic mRNA technologies represent a versatile platform that can be used to develop advanced drug products. The remarkable speed with which vaccine development programs designed and manufactured safe and effective COVID-19 vaccines has rekindled interest in mRNA technology, particularly for future pandemic preparedness. Although recent R&D has focused largely on advancing mRNA vaccines and large-scale manufacturing capabilities, the technology has been used to develop various immunotherapies, gene editing strategies, and protein replacement therapies. Within the mRNA technologies toolbox lie several platforms, design principles, and components that can be adapted to modulate immunogenicity, stability, in situ expression, and delivery. For example, incorporating modified nucleotides into conventional mRNA transcripts can reduce innate immune responses and improve in situ translation. Alternatively, self-amplifying RNA may enhance vaccine-mediated immunity by increasing antigen expression. This review will highlight recent advances in the field of synthetic mRNA therapies and vaccines, and discuss the ongoing global efforts aimed at reducing vaccine inequity by establishing mRNA manufacturing capacity within Africa and other low- and middle-income countries.